2022
DOI: 10.1128/spectrum.00807-22
|View full text |Cite
|
Sign up to set email alerts
|

Emergence, Evolution, and Biological Characteristics of H10N4 and H10N8 Avian Influenza Viruses in Migratory Wild Birds Detected in Eastern China in 2020

Abstract: The emerging avian influenza reassortants and mutants in birds pose an increasing threat to poultry and public health. H10 avian influenza viruses are widely prevalent in wild birds, poultry, seals, and minks and pose an increasing threat to human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…The YRD wetland located in Eastern China is an important habitat for migratory birds on the East Asian-Australasian (EAA) flyway. We have identified 28 subtypes of AIVs in wild birds in YRD wetland from 2017 to 2022, as shown in our previous studies [8,9,[30][31][32][33][34][35]. In this study, we fully uncovered the ecology and evolutionary dynamics of the globally identified H12 viruses.…”
Section: Introductionsupporting
confidence: 56%
“…The YRD wetland located in Eastern China is an important habitat for migratory birds on the East Asian-Australasian (EAA) flyway. We have identified 28 subtypes of AIVs in wild birds in YRD wetland from 2017 to 2022, as shown in our previous studies [8,9,[30][31][32][33][34][35]. In this study, we fully uncovered the ecology and evolutionary dynamics of the globally identified H12 viruses.…”
Section: Introductionsupporting
confidence: 56%
“…demonstrated that the acquisition of PB2 627K in mammals is driven by the low polymerase activity attributed to PA. 49 Moreover, Bhat et al showed that acquiring the PA gene from an H9N2 virus dramatically increased the polymerase activity of an H7N9 virus in human cells. 50 In terms of the rapid evolution and active reassortment of H10N3 in nature, 23,40,41 the presence of avian adaptation marker PB2 627E does not downgrade the potential cross-species transmission of H10N3 viruses.…”
Section: Discussionmentioning
confidence: 99%
“…H10N8 viruses caused three human infections between 2013 and 2014; however, no additional H10N8 human case was reported thereafter. Then, in 2021, an H10N3 human case was reported in Jiangsu, China, raising the concern of cross‐species transmission of H10 virus 10,21–23 . This case raised questions as to how the H10N3 virus has evolved to infect humans since 2014, and how much risk do H10N3 viruses pose to the poultry industry and public health.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the detection of rearrangements and mutations of the Influenza virus in wild birds, public concern about the potential pandemic risk posed by this viral species and its mutations is growing significantly ( 77 , 86 , 87 ). Indeed, evidence of transmission from avian viral species to humans has previously been described for A/H7N9, A/H6N1 and A/H10N8 variants, and approximately 35% of patients infected with A/H7N9 succumbed to zoonotic infection ( 87 ).…”
Section: Virus Reservoirs In Mammals and Birdsmentioning
confidence: 99%